Análisis de seguridad de la información basado en la norma ISO 27001 en el Área Técnica de Reparación e Instalación de la Corporación Nacional de Telecomunicaciones "CNT EP" de la ciudad de Babahoyo - Villamar Silva, Crysthian Geovanny (2021)
This case study deals with information security, which is one of the aspects to which they have managed to take one of the greatest interests in the computer field even though the computational world has become easier every day, however, the Insecurity regarding this is incremental. In this document there is a reference to the dangers and losses of one of the most important assets of companies such as information and its relationship to minimize impacts with the ISO27001 standard, since it is always important to treat them to avoid and prevent having to regret for total loss of data. This case study was oriented under the research sub-line of the systems engineering career, since the research line is the following: "Communication and business and technological undertakings, development of information systems and the sub-line is data processes and telecommunications ”. Likewise, with this case study, it has been necessary to strengthen many issues related to information security and ISO 27001 standards, where well-known technicians were also invited to participate, all systems engineers from the city of Babahoyo, who with His knowledge contributed a lot to achieve an adequate analysis that was required in this final degree project, and with this it is understood that it improves the due guarantees of technical thinking referenced by experts in the field; It should be noted that, in addition, this has been highly analyzed by the author, who added to this enriched the research with important and inherent theories in a cited and referenced way, which allowed the consolidation of the present case study. Here, in addition, annexes are included, where the various participations in the interviews are evidenced.